2020
DOI: 10.1016/j.bone.2019.115084
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy in the Col1a2G610C mouse model of Osteogenesis Imperfecta reveals an additive effect of enhancing LRP5 signaling and inhibiting TGFβ signaling on trabecular bone but not on cortical bone

Abstract: Enhancing LRP5 signaling and inhibiting TGFβ signaling have each been reported to increase bone mass and improve bone strength in wild-type mice. Monotherapy targeting LRP5 signaling, or TGFβ signaling, also improved bone properties in mouse models of Osteogenesis Imperfecta (OI). We investigated whether additive or synergistic increases in bone properties would be attained if enhanced LRP5 signaling was combined with TGFβ inhibition. We crossed an Lrp5 high bone mass (HBM) allele (Lrp5 A214V ) into the Col1a2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Previous work in preclinical models has shown that increased TGF-β signaling is a pathogenetic mechanism in OI caused due to alterations in type I collagen and that inhibition of TGF-β could be of therapeutic benefit ( 25 , 30 32 ). In order to facilitate clinical translation, we first profiled the transcriptome of human OI bone.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work in preclinical models has shown that increased TGF-β signaling is a pathogenetic mechanism in OI caused due to alterations in type I collagen and that inhibition of TGF-β could be of therapeutic benefit ( 25 , 30 32 ). In order to facilitate clinical translation, we first profiled the transcriptome of human OI bone.…”
Section: Discussionmentioning
confidence: 99%
“…Despite decades of research, current therapeutic strategies to address OI still have many deficits 70, 71 . The most common clinical approach involves treatment with anti-resorptive agents, most prominently the bisphosphonates 71 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to inhibitors of catabolism, inducers of bone anabolism have recently received increasing attention. Of particular significance, increasing bone production via enhancing LRP5 signaling genetically or by targeting sclerostin and using antibodies to inhibit TGFß signaling have both shown promise, with the TGFß-targeting strategy currently in clinical trials 54, 70, 72, 73 . Prior work has also suggested the potential of the chemical chaperone 4-phenylbutyric acid to ameliorate skeletal defects in an OI zebrafish model 74, 75 .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the model has been used to investigate the role of mutant collagen in causing OI symptoms such as growth deficiencies [11], defective mineralization of developing bone [12], disrupted osteoblast differentiation [13], and impaired fracture healing [14]. It has also been used in preclinical trials of OI treatments such as upregulating the LRP5 pathway [15,16], diet-based attempts to degrade mutant procollagen and thereby increase bone strength [17,18], sclerostin antibody and zoledronate combination therapy [19], bone marrow transplant [20], TGF-beta inhibition [16,21], activin receptor inhibitor treatment to improve muscle contractility [22], myostatin inhibition [23], and BMP-2 injections for fracture healing [24].…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies are limited in what data are reported and how sex is considered (most examine male or female mice, rarely both). They typically do not report more than basic structural mechanics-most commonly ultimate load, stiffness, and energy to ultimate load [16][17][18][19][20]23]. Since the incorporation of mutant collagen in the bone matrix is the primary cause of OI's brittle phenotype, tissue-level mechanical properties (e.g.…”
Section: Introductionmentioning
confidence: 99%